Imperfect Financial Markets as a Commitment Device for the Government - Jenny Simon (Center for Economic Studies and ifo Institute (CESifo), 2014)
When the government lacks the ability to commit to a tax policy over time, agents' involvement in imperfect financial markets can be welfare improving. Agents borrow against their promised income in markets that are incomplete in the sense that claims cannot be resold without loss. Taking these contractual positions into account thus changes the government's ex-post incentives to renege on the promised tax schedule. Any increase in redistribution ex-post would lead to some agents not being able to fulfill their financial liabilities. The impending individual default losses add up to an effective commitment device for the government. Even a small market imperfection yields limited commitment, which leads to optimal partial pooling in the tax schedule.
Keywords: E61; H21; D82; 330; limited commitment; commitment device; financial markets; incomplete markets; revelation theorem; redistribution Mirrlees